THE VOICES OF THE WAR (“EPITAPHS OF THE WAR” BY R. KIPLING) - Tetiana M. Potnitseva (Вісник університету ім. А. Нобеля. Серія Філологічні науки)
The article is examined R. Kipling’s “Epitaphs of the War” (1919) appeared as a summing up of his experience during the First World War. The work reflects the writer’s feeling of tragedy and grandiosity of that historical event. Kipling himself witnessed many episodes of the war and survived his personal tragedy – the death of his son John in 1915. The article aims to analyze the genre originality of the epitaph in the context of R. Kipling’s anti-war theme. Although this part of Kipling’s creative heritage remains less well-known, it is attracting the attention of Ukrainian literary critics and translators now. To reveal the specificity of that poetic work, the comparative and historical-literary methods are applied. The original form of the epitaphs is presented as an epigram which allows one to hear either a voice of a perished soldier or of someone who is reading the epitaph. This manner – not to depict and explain but to transcribe reality – is very recognizable of Kipling’s “masculine style”. In such a manner the first English laureate of the Noble Prize creates a diverse picture of the War in a variety of its tragic episodes and men’s destinies. Thus, a universal picture is born and the main conclusions of the author become transparent. Kipling creates a generalized image of the War by depicting those incredible variants of death “in which life may be extinguished” (J.M.S. Tompkins). Among the dead – “the beginner”, who didn’t realize yet that the war was a reality, not a game as well as the 18 years old soldier of the Royal Air Force (“R.A.F. (Aged Eighteen)”); the sentinel who falls asleep on his post (“The Sleepy Sentinel”); the one who was afraid to face death (“The Coward”) and was severely punished for that by his own combatants and many other tragic stories of the war. The climax of the cycle is the one epitaph in which Kipling formulates his main conclusion about the war – it is “Common Form”. The very title of this epitaph could be interpreted as a “generally used form of explanation” which in Kipling’s ironical presentation is identical to “the main conclusion”. His personal summing up of the event is formulated in the final words: “If any question why we died / Tell them, because our fathers lied”. Namely in these words personal and universal meet. Kipling had feelings of guilt about pushing his son to go to war. At that time, he was captured by patriotic illusions as well as many writers of his country. The perception of the War as a great battle for national and human freedom was the ground on which the main pathos of the War was formed. It penetrated the literary works, the mood of people and resulted in the main myth that appears at any war. Conclusion. The voices of the perished in the First World War that sound in Kipling’s epitaphs create not only the general image of that historical event but a penetrating image of any military confrontation of people, in which human victims, losses and tragedies are inevitable. His epitaphs, without doubt, are relevant in our modern context as well. In addition, they demonstrate different sides of writers’ possible participation in the event in dynamics: from war propagandist to quite another estimation of the war due to one’s personal experience. The poetological peculiarity of Kipling’s epitaphs is in his return to the antique tradition of genre interpenetration of epigram and epitaph. That is what makes the writer’s style recognizable as well as his intention not to depict or comment but to “decipher” the living reality in many shades out of which the wholeness of the world is created. In the interpretation of death, the emphasis is shifting from the philosophical to humanitarian and social-political one. Instead of memento mori (transient of earthly existence), Kipling focuses his attention on the violent death during the war (correlating and identifying the image of war and the image of death) which is presented as a vain sacrifice in the name of someone’s interests. Instead of the idea of equality of death and sacrifice or traditional philosophical meditations about death as an eternal peace, a stay in eternity, Kipling gives a whole spectrum of emotional-expressive connotations connected with his perception of the war – fear, horror, murder, sensation of shock got of imagining what the dead thought and felt at the last moment of their life. Kipling’s epitaphs present the dead soldiers’ voices addressed to contemporaries and descendants containing not only their personal experience of some concrete episodes of the war but a generalized summing up of the war with its senseless sacrifices and by that giving a kind of warning to those who are alive. The theme of lies and far-fetched ideals and their illusory character as well as the theme of false patriotism dominates in Kipling’s epitaphs adding the traces of civic lyrics to that genre. The structural basis of epitaphs is a couplet close to the epigram and a quatrain with a philosophical generalization. Irony is recognizable key artistic modus of Kipling with the help of which he creates a certain character type of the real world simultaneously giving his estimation of the emerging concept of the world which he obviously rejects.